2019
DOI: 10.4103/ajns.ajns_79_18
|View full text |Cite
|
Sign up to set email alerts
|

The importance of measuring mamillopontine distance as a diagnostic criterion of hydrocephalus degrees

Abstract: Objectives:The occurrence of obstructive hydrocephalus (ObH) as sequelae of deep midline brain tumors (third and lateral ventricles, thalamic, pineal region, brainstem, and fourth ventricle) can be estimated up to 90% of cases. We believe that the mamillopontine distance (MPD) – the distance between the lower surface of the mammillary body and the upper surface of the pons in the sagittal images – can be a sufficiently reliable alternative to the Evans’ index (EI) for the diagnosis of ObH.Patients and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…The mammilopontine distance is the shortest distance between the inferior margin of the mammillary bodies and the superior surface of the pons, measured in mid-sagittal T1-weighted images. It is normally around 7 mm [9] or even 9 mm [10], whereas in our patient it was 6.7 mm. In addition, the pituitary gland was enlarged and hyperemic.…”
Section: Follow-upcontrasting
confidence: 62%
See 1 more Smart Citation
“…The mammilopontine distance is the shortest distance between the inferior margin of the mammillary bodies and the superior surface of the pons, measured in mid-sagittal T1-weighted images. It is normally around 7 mm [9] or even 9 mm [10], whereas in our patient it was 6.7 mm. In addition, the pituitary gland was enlarged and hyperemic.…”
Section: Follow-upcontrasting
confidence: 62%
“…The mammilopontine distance is the shortest distance between the inf margin of the mammillary bodies and the superior surface of the pons, measured in sagittal T1-weighted images. It is normally around 7 mm [9] or even 9 mm [10], whe in our patient it was 6.7 mm. In addition, the pituitary gland was enlarged and hypere In our view, the main diagnostic possibilities at this stage were idiopathic pachym ingitis or secondary pachymeningitis (either in Wegener granulomatosis-considerin persisting nasal discharge or an IgG4-related one).…”
Section: Follow-upmentioning
confidence: 43%
“…Kariev et al (2019) reported that MPD is an alternative measurement with high specificity in the diagnosis of obstructive hydrocephalus [ 10 ]. In another study with 43 patients and 30 control groups, the mean MPD value of the patient group was found to be 3.4 mm and 9.8 mm in the control group [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pontomesencephalic angle (PMA) and mamillopontine distance (MPD) have been found useful in the diagnosis of intracranial hypotension. It has also been reported that MPD is a useful aid in the diagnosis of hydrocephalus [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 97%